George Kateb dignity, morality, individuality - Kateb, George 1931- (Routledge innovators in political theory, 2015)
"George Kateb's writings have been innovatory in exploring the fundamental quandary of how modern democracy...sovereignty vested in the many...might nevertheless protect, respect, promote, even celebrate the singular, albeit ordinary individual. His essays, often leading to unexpected results, have focused on many inter-related topics: rights, representation, constitutionalism, war, evil, extinction, punishment, privacy, patriotism, and more. This book focuses in particular on his thought in three key areas: Dignity These essays exhibit the breadth and complexity of Kateb's notion of dignity and outline some implications for political theory. Rather than a solely moral approach to the theory of human rights, he elaborates a human-dignity rationale for the very worth of the human species Morality Here Kateb challenges the position that moral considerations are often too demanding to have a place in the rough-and-tumble of modern politics and political analysis. Rejecting common justifications for the propriety of punishment, he insists that state-based punishment is a perplexing moral problem that cannot be allayed by repairing to theories of state legitimacy. Individuality These essays gather some of Kateb's rejoinders and correctives to common conceptions and customary critiques of the theory of democratic individuality. He explains that Locke's hesitations and religious backtracking are instructive, perhaps as precursors for the ways in which vestigial beliefs can still cloud moral reasoning. "..